Prenatal origin of childhood AML occurs less frequently than in childhood ALL - Burjanivová, Tatiana; Madžo, Jozef; Mužíková, Kateřina; Meyer, Claus; Schneider, Bjoern; Votava, Felix; Marschalek, Rolf; Starý, Jan; Trka, Jan; Zuna, Jan (BMC cancer, 2006)
BACKGROUND: While there is enough convincing evidence in childhood acute lymphoblastic leukemia (ALL), the data on the pre-natal origin in childhood acute myeloid leukemia (AML) are less comprehensive. Our study aimed to screen Guthrie cards (neonatal blood spots) of non-infant childhood AML and ALL patients for the presence of their respective leukemic markers. METHODS: We analysed Guthrie cards of 12 ALL patients aged 2-6 years using immunoglobulin (Ig) and T-cell receptor (TCR) gene rearrangements (n = 15) and/or intronic breakpoints of TEL/AML1 fusion gene (n = 3). In AML patients (n = 13, age 1-14 years) PML/RARalpha (n = 4), CBFbeta/MYH11 (n = 3), AML1/ETO (n = 2), MLL/AF6 (n = 1), MLL/AF9 (n = 1) and MLL/AF10 (n = 1) fusion genes and/or internal tandem duplication of FLT3 gene (FLT3/ITD) (n = 2) were used as clonotypic markers. Assay sensitivity determined using serial dilutions of patient DNA into the DNA of a healthy donor allowed us to detect the pre-leukemic clone in Guthrie card providing 1-3 positive cells were present in the neonatal blood spot. RESULTS: In 3 patients with ALL (25%) we reproducibly detected their leukemic markers (Ig/TCR n = 2; TEL/AML1 n = 1) in the Guthrie card. We did not find patient-specific molecular markers in any patient with AML. CONCLUSION: In the largest cohort examined so far we used identical approach for the backtracking of non-infant childhood ALL and AML. Our data suggest that either the prenatal origin of AML is less frequent or the load of pre-leukemic cells is significantly lower at birth in AML compared to ALL cases.
Keywords: Male; genová přestavba B-lymfocytů; Fetal Blood; novorozenecký screening; Core Binding Factor Alpha 2 Subunit; DNA nádorová; nádorové proteiny; Cohort Studies; polymerázová řetězová reakce; Infant; Biomarkers, Tumor; protein PEBP2A2; duplikace genu; kojenec; fms-Like Tyrosine Kinase 3; buněčné klony; Precursor Cell Lymphoblastic Leukemia-Lymphoma; akutní lymfatická leukemie; Gene Rearrangement, T-Lymphocyte; ženské pohlaví; DNA, Neoplasm; Gene Rearrangement, B-Lymphocyte; předškolní dítě; Polymerase Chain Reaction; myeloidní leukemie; Leukemia, Myeloid; Infant, Newborn; Child, Preschool; kohortové studie; novorozenec; genová přestavba T-lymfocytů; tandemové repetitivní sekvence; Humans; Myeloid-Lymphoid Leukemia Protein; dítě; nádorové biomarkery; tyrosinkinasa 3 podobná fms; Child; Female; Financing, Organized; mužské pohlaví; protoonkogenní protein MLL; Neoplasm Proteins; financování organizované; fúzní onkogenní proteiny; Gene Duplication; Tandem Repeat Sequences; fetální krev; Bone Marrow Cells; Neonatal Screening; lidé; buňky kostní dřeně; Clone Cells; Oncogene Proteins, Fusion